2006
DOI: 10.1056/nejmoa051779
|View full text |Cite
|
Sign up to set email alerts
|

Transcoronary Transplantation of Progenitor Cells after Myocardial Infarction

Abstract: Intracoronary infusion of progenitor cells is safe and feasible in patients with healed myocardial infarction. Transplantation of BMC is associated with moderate but significant improvement in the left ventricular ejection fraction after 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
639
1
12

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 977 publications
(666 citation statements)
references
References 22 publications
14
639
1
12
Order By: Relevance
“…For example, the MAGIC II trial of skeletal myoblast transplantation into chronic infarcts was terminated early by the study's data safety monitoring board, because the treatment offered no benefit on ejection fraction compared to placebo [29]. Similarly, delivery of bone marrow cells to patients with acute MI has produced mixed results, with two negative trials [30,31], one showing transient benefit [32] and one showing sustained benefit [33]. The reasons for this failure to translate preclinical results into benefits in humans are not known, but a good candidate is the vast difference in cell number required for human therapy compared to rodents.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the MAGIC II trial of skeletal myoblast transplantation into chronic infarcts was terminated early by the study's data safety monitoring board, because the treatment offered no benefit on ejection fraction compared to placebo [29]. Similarly, delivery of bone marrow cells to patients with acute MI has produced mixed results, with two negative trials [30,31], one showing transient benefit [32] and one showing sustained benefit [33]. The reasons for this failure to translate preclinical results into benefits in humans are not known, but a good candidate is the vast difference in cell number required for human therapy compared to rodents.…”
Section: Introductionmentioning
confidence: 99%
“…43,53,54,62 Heart Failure Additionally, there have been multiple HF trials (Table 2). Many demonstrated benefits in ventricular function noted by increased EF, [68][69][70][71][72][73]75,79,82,83 improved functional class, 75,78,80,82,83,86 reduced infarct size, 70,72,80,[82][83][84] decreased mortality, 79 and acceptable safety outcomes. [66][67][68][69]75,78,80,[82][83][84]86 SCIPIO was the first trial using autologous CSC in HF and showed improvement in EF, infarct size, viable tissue, and HF scores.…”
Section: Clinical Outcomes Acute Myocardial Infarctionmentioning
confidence: 99%
“…Patients were derived from 2 study cohorts with the same inclusion criteria. 15,16 The ethics committee of the J.W. Goethe University reviewed and approved the study protocols.…”
Section: Patient Populationmentioning
confidence: 99%